Variasi Bahasa dalam Film Catatan Menantu Sinting: Studi Perbedaan Dialek dalam Interaksi Keluarga: Studi Perbedaan Dialek dalam Interaksi Keluarga - Muhammad Abrar; Latifah Qorimahtul Fajri; Syahrul Ramadhan; Elfia Sukma; Norliza Jamaluddin (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This research aims to analyze language variation, especially dialect, in the film Catatan Menantu Sinting and its influence on communication and relationships between characters in the family. The method used in this research is a qualitative approach with documentation techniques to observe the characters' conversations in the movie that contain dialect variations. The focus of the research is on the difference in dialect between the son-in-law character who uses standard Indonesian and the mother-in-law character who uses Minang dialect, as well as its impact on social and cultural relationships between family members. The results show that the use of dialect in this film serves as a tool to illustrate the differences in social status, education, and cultural identity of the characters, as well as enrich their characterization. Besides that, dialect variations also affect the dynamics of communication in the family, by creating tension or closeness between characters. The use of code switching between formal language and local dialect also illustrates social adaptation and attempts to create familiarity in family relationships. Overall, this study reveals that dialect not only functions as a tool of communication, but also as a reinforcement of characterization and social dynamics in films.